PIPELINE PROGRAM CDM DI INDONESIA: SEBUAH PELUANG DAN TANTANGAN UNTUK INDUSTRI PERTAMBANGAN - Joni Safaat Adiansyah (Jurnal Teknosains, 2011)
Climate change is one of the world’s problems that must be dealt; the failure in tackling climate change will impact on increasing the earth temperature and endanger the archipelago countries including Indonesia. Clean Development Mechanism (CDM) is one of the Kyoto Protocol mechanisms designed to mitigate climate change. Indonesia is one of the countries that meets the requirement as the host of CDM program and has set up the target to reduce GHG emissions as much as 26 percent in year 2020. The industrial sector has opportunities to engage actively in reducing GHG emission including mining industry.  The objectives of this research are to find out the potency of mining company’s involvement in climate change mitigation efforts particularly through CDM. In addition, the research of method that is chosen is literature study including reviewing data relating to CDM and with qualitative approached. The result shows that mining industry has a potency to involve actively in CDM program, among others, through energy efficiency, fuel substitution, renewable energy, Coal Bed Methane and the handling of critical lands through afforestation and reforestation scheme. Furthermore, by using Business as Usual assumption, the linier  regression that is produced y=27.255.x + 12.711 therefore  It is estimated that about 15 Mt CO2-e (assuming 4 percent reduction) needs to be derived from the energy sector in 2020 that can be taken as an opportunity for the mining industry as well.